THE INFLUENCE OF PROFESSIONAL COMMITMENT AND WORK COMPETENCY ON CAPTAIN'S PERFORMANCE IN THE OPERATION OF AUTOMATIC IDENTIFICATION SYSTEM (AIS) - Wijaya, Hendra; Malau, April Gunawan; Motik, Chandra (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the effect of professional commitment and work competence on captains' performance in operating the Automatic Identification System (AIS) on the BPSDM Transportation Training Ship. This research uses the mixed methods method, which is a research step combining two forms of research that have existed before, namely qualitative and quantitative research. The data analysis used is structural equation modelling-partial least squares (SEM-PLS) using SmartPLS software. The results showed that the factors influencing professional commitment and work competence on the captain's performance in the operation of the Automatic Identification System (AIS) on the BPSDM Transportation Training Ship included; Personal Factors, Situational Factors, Positional Factors and Team Factors and situations